Divergence of duplicate POMC genes in gilthead sea bream Sparus auratus - Cardoso, João (2014)
Proopiomelanocorticotrophin (POMC) in vertebrates is produced in the pituitary gland and undergoes post-translational processing to give rise to a range of biologically active peptides. Teleosts possess 2–3 different POMC transcripts which have been proposed to have originated from a whole or partial genome duplication. In the present study 2 transcripts of gilthead sea bream POMC (sbPOMC-a1 and a2) were cloned and characterised. sbPOMC-a1 is expressed principally in the melanotroph cells of the pars intermedia (PI) and sbPOMC-a2 is expressed in the corticotroph cells of the rostral pars distalis and probably also in the PI. The 2 sbPOMC transcripts have a differential tissue distribution in extra-pituitary sites. An appraisal of POMC evolution indicates sbPOMCs belong to one of the two main clades that exist in teleosts and that overall a non conservative process of gene loss occurred in this infraclass.